2003
DOI: 10.1063/1.1578152
|View full text |Cite
|
Sign up to set email alerts
|

Fiber optic reflectometer for velocity and fraction ratio measurements in multiphase flows

Abstract: Reply to "Comment on 'Fiber optic reflectometer for velocity and fraction ratio measurements in multiphase flows' " [Rev. Sci. Instrum. 74, 3559 (2003)] Rev. Sci. Instrum. 75, 286 (2004); 10.1063/1.1634361Comments on "Fiber optic reflectometer for velocity and fraction ratio measurements in multiphase flows" [Rev.A technique based on the coherent mixing of scattered signal with Fresnel reflection signal from the tip of an optical fiber is used to demonstrate the feasibility of measuring the velocity and fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 18 publications
1
48
0
1
Order By: Relevance
“…Generally, the optical probe is considered rather accurate in terms of void fraction. Comparing optical probe results with other measurement techniques (i.e., visual or pressure sensors), the relative differences found in the literature are as follows: between À 0.8% and À 16% (Barrau et al, 1999), À2.2% (Zhang and Zhu, 2013), -3% (Chang et al, 2003), À 11% (Lima Neto et al, 2008), between À6 and À 14% (Kiambi et al, 2003), þ 12% (Simonnet et al, 2007). Barrau et al observed the worst performance with no liquid flow and/or at low gas fractions.…”
Section: Optical Probe Sources Of Errorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the optical probe is considered rather accurate in terms of void fraction. Comparing optical probe results with other measurement techniques (i.e., visual or pressure sensors), the relative differences found in the literature are as follows: between À 0.8% and À 16% (Barrau et al, 1999), À2.2% (Zhang and Zhu, 2013), -3% (Chang et al, 2003), À 11% (Lima Neto et al, 2008), between À6 and À 14% (Kiambi et al, 2003), þ 12% (Simonnet et al, 2007). Barrau et al observed the worst performance with no liquid flow and/or at low gas fractions.…”
Section: Optical Probe Sources Of Errorsmentioning
confidence: 99%
“…Moreover, this measurement period is far above the typical values of 1-5 min for similar optical probes (Chang et al, 2003;Chaumat et al, 2005a;Lima Neto et al, 2008;Zhang and Zhu, 2013).…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…• Void fraction: Comparing optical probe results with other measurement techniques (i.e., visual or pressure sensors), it is generally found that the underestimation of the local value and the relative differences is between À0.8% and À16% [33,[36][37][38][39]. It is worth noting that Simonnet et al [34] observed an overestimation of the optical probe value of þ12%.…”
Section: Optical Probe Errorsmentioning
confidence: 99%
“…신호의 시계열로부터 위상 상 태를 검토하고 지속시간을 바탕으로 공극률 및 크기를 추 정한다 (Chanson, 1997). 전도도식 장치 외에 위상차에 신 호변화를 나타내는 광섬유를 활용한 기법도 연구에 사용 되고 있다 (Chang et al, 2002;Chang et al, 2003). Chang et al (2003) (Ryu et al, 2007 (Chanson, 1997;Jung and Ryu, 2012 …”
unclassified